2012
DOI: 10.1089/thy.2011.0258
|View full text |Cite
|
Sign up to set email alerts
|

Anaplastic Transformation of Follicular Thyroid Carcinoma in a Metastatic Skeletal Lesion Presenting with Paraneoplastic Leukocytosis

Abstract: To our knowledge, this is the first case of anaplastic transformation of DTC arising in a metastatic bone lesion described in the literature. In addition, the present case also exhibited severe leukocytosis accompanied by elevated serum G-CSF levels. Clinicians should be aware of the possibility of this occurring in their patients with DTC, as this development calls for a rapid change from observational follow-up to aggressive treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 31 publications
2
19
0
Order By: Relevance
“…Anaplastic transformation may also take place in a metastatic focus, (Figures 9(a), 9(b), and 9(c)) thus supporting the idea that these lesions originate through the dedifferentiation of preexisting well-differentiated cancer [8789]. …”
Section: Histogenesissupporting
confidence: 56%
“…Anaplastic transformation may also take place in a metastatic focus, (Figures 9(a), 9(b), and 9(c)) thus supporting the idea that these lesions originate through the dedifferentiation of preexisting well-differentiated cancer [8789]. …”
Section: Histogenesissupporting
confidence: 56%
“…Kaushal et al [10] reported that anaplastic transformation developed in the shoulder 8 years after diagnosis of PTC, and, clinically and pathologically, it mimicked soft tissue sarcoma. Nakayama et al [11] reported anaplastic transformation of follicular carcinoma in pelvic metastasis 12 years after initial diagnosis. The ATCCJ was established to compile data and analyze treatment outcomes of ATC cases from Japan [4].…”
Section: Discussionmentioning
confidence: 99%
“…To date, fewer than 20 cases of anaplastic transformation at the metastatic sites have been reported in the English literature [1,[4][5][6][7][8][9][10][11]. Here, we report an additional case of anaplastic transformation which developed in the pleural metastasis, combined with a literature review.…”
Section: Introductionmentioning
confidence: 95%
“…As in other solid tumours, leukemoid reactions are caused by abnormal production of haematopoietic cytokines from tumour cells including GM-CSF and G-CSF also in thyroid cancer patients 7. Circulating levels of G-CSF and GM-CSF were not measured directly in our patient; however, sensory neuropathy of new onset and its persistence during the development of extreme leucocytosis in a patient whose WBCs had always been in the normal range below 10 000/mm 3 as documented over several years makes it very likely that paraneoplastic release of myelopoietic growth factors was in fact responsible also for his increased pain sensitivity.…”
Section: Discussionmentioning
confidence: 99%